VD_FINDINFO 153/2012/DCA vom 20. Dezember 2012 - VD Tribunal cantonal (2012)
FRAIS D'EXPERTISE, SUSPENSION DE LA PROCÉDURE, MORT, MANDAT, AVOCAT | 405 CO, 242 al. 1 CPC, 242 al. 2 CPC, 242 CPC, 63 al. 1 CPC, 63 CPC